Immediate Manager Gender and Female Wages - The Importance of Manager Position - Karin Halldén; Jenny Säve-Söderbergh; Asa Rosen (Center for Economic Studies and ifo Institute (CESifo), 2016)
One argument for increasing female representation in management is the anticipation that female managers are particularly beneficial for female employees through, e.g., role modeling or mentoring. Contrary to the expected positive association, we find that female wages are negatively associated with working directly for a female as opposed to male manager using a representative sample of matched employee-employer data from Sweden. However, dividing the sample by managerial position, and controlling for important sorting of employees, the negative association is found only among lower-level managers and not among high-level managers. We discuss decision-making power as one possible explanation for this heterogeneity.
Keywords: J16; J31; J53; J71; 330; gender of manager; female wages; immediate manager